2021
DOI: 10.1007/s10620-021-07141-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Randomized Controlled Trials of Fecal Microbiota Transplantation in Recurrent Clostridioides difficile Infection

Abstract: Introduction Clinical trials have demonstrated the efficacy of FMT for reduction in CDI recurrences (rCDI), but this treatment and its reporting in the literature has significant heterogeneity. Recent publications (e.g., Ramai et al. in Dig Dis Sci 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The higher threshold therefore corresponds to a statistically very persuasive finding. The lower threshold provides evidence of a statistically significant phase III trial (see ESM, pages [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher threshold therefore corresponds to a statistically very persuasive finding. The lower threshold provides evidence of a statistically significant phase III trial (see ESM, pages [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled and controlled clinical trials report FMT as an effective treatment for rCDI [11]. While these foundational trials have indicated treatment success for microbiota restoration in patients with rCDI [12], they suffer from significant heterogeneity [11,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fecal microbiota transplantation has shown a 90% success rate ( Borgia et al, 2015 ), additional efforts are needed to address safety concerns and other technical improvements ( Wang et al, 2016 ; Shin et al, 2018 ; DeFilipp et al, 2019 ). New preventive and therapeutic approaches are currently being developed as live biotherapeutic products (LBPs), including numerous capsule-based standardized microbiota restoration approaches ( Feuerstadt et al, 2021 ; Khanna et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The liver phenotype is based on histological features that also have similar presentations in humans ( Figure 1 ). Metabolic disorder phenotype describes various systemic disorders of the animal models that are also presented in MAFLD: (i) obesity refers to significantly increased body weight from control, (ii) diabetes, (iii) insulin resistance is tested via glucose tolerance tests, introduced intraperitoneally, intravenously or orally [ 170 ], and (iv) dyslipidemia refers to increased plasma cholesterol levels, increased plasma triglycerides, cholesterol, low-density lipoprotein (LDL) and/or decreased high-density lipoprotein (HDL). Due to the cumulative and temporal nature of the animal models, these characteristics are described in terms of the earliest duration of feeding reported in the model, from the start time of the model, that is, the time of diet initiation.…”
Section: Mafld Preclinical Modelsmentioning
confidence: 99%